Remettre en acte des extraits d’ethnographie - Marie Mazzella di Bosco (Ateliers d'Anthropologie)
Taking up one’s ethnographic data again with the aim of (re)creating, not a scene that would be performed as in a theatre, but conditions conducive to an experience similar to that which was observed and lived through as an ethnographer, sheds much light not only on the data itself, but also on its production methods and on the researcher's positioning. Among other benefits, the process of re-enactment brings to the fore a set of knowledge and know-how incorporated by the ethnographer, which goes beyond the field notebooks and other collected materials. The article first recounts an experiment, in which volunteer colleagues and students put into practice some of the material from fieldwork on “free-form mindful dances”, in order to re-examine their description and analysis with more acuity, and then it offers a reflexive look at the heuristic, dialectical and illustrative benefits of such a re-enactment.